Najnowsze światowe standardy w diagnostyce stwardnienia rozsianego - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The diagnosis of multiple sclerosis (MS), one of the major causes of neurologic-based disability in young adults, is challenging because of the heterogeneity of signs and symptoms, many of which are not specific to MS, and because there is no single test to verify MS. During the last 40 years, the diagnosis of multiple sclerosis has been aided by increasing knowledge of the natural history and pathophysiology of the disease and by technologic advances in clinical, laboratory and radiologic testing. This report describes the evolution of MS diagnostic guidelines for physician in clinical practice with a focus on recent recommended criteria from the year 2005, called “Revised McDonald Criteria”.